Adolescent pregnancy prevention programs in Latin America from an intersectional approach. Systematic review - Librado-González, Natanael (2024)
Introduction: intersectionality in health offers a fundamental analytical framework for understanding social inequities. This approach is essential for inclusion in adolescent pregnancy prevention programs in Latin America. Objective: To conduct a systematic review of adolescent pregnancy prevention programs in Latin America from an intersectional approach. Material and methods: PRISMA guidelines and the Cochrane Handbook for systematic reviews of interventions were followed. The search encompassed randomized controlled trials in English, Spanish, and Portuguese in databases such as PubMed, Cochrane, BIREME, BVS, LILACS, ERIC, PsycINFO, SCOPUS and Google Scholar. Case-control, cohort, and quasi-experimental studies were excluded. Risk of bias was assessed using the Cochrane RoB2 tool. Data were analyzed using descriptive statistics and measures of effect. The protocol was registered in PROSPERO (CRD42024540325). Results: Seven studies with 16 873 participants were reviewed. One of them highlighted the intersectional importance in the prevention of adolescent pregnancy by addressing sexual and gender diversity. The other studies showed that educational and self-efficacy interventions can increase condom use, improve sexual assertiveness, reduce pregnancy and sexual initiation rates, and improve contraceptive knowledge. Discussion: There is a gap in the consideration of intersectionality. There is limited evidence of effectiveness of interventions to prevent adolescent pregnancy, lacking robust evidence in intersectional strategies. Conclusions: The review underscores the importance of inclusive and integrative approaches to effectively address inequalities in adolescent pregnancy prevention.